2014
DOI: 10.1039/c3ra46287k
|View full text |Cite
|
Sign up to set email alerts
|

Modified nanofibrillated cellulose–polyvinyl alcohol films with improved mechanical performance

Abstract: In this study chemically surface-modified nanofibrillated cellulose (NFC) was used at low levels (0.5 to 3 wt%) as reinforcement in a polyvinyl alcohol (PVA) matrix. The modified NFC-PVA films prepared by a solution casting technique showed improved mechanical performance and good optical properties. NFC was allylated and further epoxidised with hydrogen peroxide. The addition of 1 wt% epoxy-NFC enhanced the modulus and strength of the pure PVA film, 474% and 224%, respectively. This composite film exhibited v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 53 publications
2
39
0
1
Order By: Relevance
“…Hence, the stabilization of PVA polymer using a variety of additives is needed. Previous studies have confirmed that strong interfacial interaction is useful for acquiring excellent reinforcement effects . In this work, a systematic study have been carried out on the effect of LS additive concentration on the optical properties of PVA and concurrently correlated to the produced structural changes as revealed via X‐ray diffraction (XRD) analysis.…”
Section: Introductionmentioning
confidence: 93%
“…Hence, the stabilization of PVA polymer using a variety of additives is needed. Previous studies have confirmed that strong interfacial interaction is useful for acquiring excellent reinforcement effects . In this work, a systematic study have been carried out on the effect of LS additive concentration on the optical properties of PVA and concurrently correlated to the produced structural changes as revealed via X‐ray diffraction (XRD) analysis.…”
Section: Introductionmentioning
confidence: 93%
“…Poly(vinyl alcohol) (PVA) is a water soluble, non‐toxic, biodegradable, and biocompatible polymer that has been studied intensively in many research industries including drug‐delivery systems and artificial biomedical devices. However, hydrophilic nature and insufficient mechanical properties of PVA seriously limit its wider application . In the present study, PVA/POSS hybrid nanocomposite membranes were prepared by solution casting method.…”
Section: Introductionmentioning
confidence: 99%
“…However, hydrophilic nature and insufficient mechanical properties of PVA seriously limit its wider application. [10][11][12][13][14] In the present study, PVA/POSS hybrid nanocomposite membranes were prepared by solution casting method. Two types of POSS were used for the present study, anionic-octa(tetramethylammonium) (Octa-TMA) and poly(ethylene glycol) (PEG) functionalized POSS.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] There are some problems faced by researchers in this eld, most of them are related to the highly polar surface of cellulose, which causes its low interfacial compatibility with non-polar polymeric matrices and the ensuing ber aggregation. 8 Typically, the use of coupling agents and the esterication of cellulose with fatty acids are two major approaches to improve interfacial interaction between cellulose and polymeric matrices. 8 Typically, the use of coupling agents and the esterication of cellulose with fatty acids are two major approaches to improve interfacial interaction between cellulose and polymeric matrices.…”
Section: Introductionmentioning
confidence: 99%